MORE THAN JUST KNOWLEDGE: HOW EXPERIENCE SHAPES UNIVERSITY STUDENTS’ DECISIONS ON DRINKING WATER - Fauziah, Ainnur Rohmah; Anwar, Tezza Adriansyah; Samoedra, Artarina Dewi Asri; Trihapsoro, Iwan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
The purpose of this study is to examine the influence of knowledge and experiential marketing on the decision to consume water. This study also aims to analyse the effect of each variable on consumption decisions and to increase students’ awareness of healthy lifestyle practices. Hospital Administration students are expected to serve as role models in promoting healthy behaviour. This study employed a descriptive-verificative design. The population consisted of Hospital Administration students at the Faculty of Medicine, Jenderal Achmad Yani University. The minimum sample size was determined to be 174 respondents; however, 189 respondents were obtained. Data were collected through literature review and questionnaires and analysed using path analysis. The results indicate that students have good knowledge of the health benefits of drinking water, although their understanding of the recommended intake remains limited. Experiential marketing has a positive and significant influence on students’ decisions, while knowledge does not show a significant effect. Simultaneously, both variables significantly influence decision-making. These findings suggest that efforts to increase water consumption should prioritise experiential strategies supported by social and environmental factors.